Linguistic Profile Test (LPT) - Normative data for children in Grades I to V - Suchitra M.G.; Prathibha Karanth (Journal of All India Institute of Speech and Hearing, 1990)
The study focussed on the collection of normative data for school going children from Grade I to Grade V for the Linguistic Profile Test (LPT). 150 children ranging in age from 6+ years to 10+ years were the subjects in the current study. There were 30 subjects in each age group. Mean and standard deviation of LPT scores (total scores) were calculated. Mean and standard deviations of each of the three sections (Phonology, Syntax and Semantics) of LPT was also obtained. The normative data would be useful in identifying children with language disorders at particular linguistic, levels and also as a baseline for speech language therapy.The qualitative analysis of the data were in line with the descriptive studies on the aspects of language i.e, Phonology, Syntax and Semantics. Mean score for the Phonology section was higher when compared to the other two sections, confirming the earlier findings that Phonological development was almost complete by the time the child reaches 6 years and beyond this the same level was maintained. As chance factor was high in the younger age groups in grammalicality judgement tasks (in the syntax section), the Grammatical Sensitivity Index (A') was calculated The Sensitivity Index indicated an increase in grammatical sensitivity with an increase in age, confirming the findings of the earlier study that adult like sensitivity was acquired by adolescence. The findings in the semantic section were also similar to those in the syntax section. Statistical analysis (Newman I Keul' s Range Test i indicated significant difference among most of the age groups (excepts 6+ & 7+) for total scores as well as for each of the three sections of LPT, confirming the findings of the earlier studies that a developmental trend was evident among age groups with-a rise at about 8 years and tending to slow down at about 10 years of age. The findings of the current study are in line with those of other investigators who equate metalinguistic awareness with other skills which emerge later in childhood at which stage the child gives evidence of the ability to formulate and make judgements about language.